Measurement of Optic Nerve Sheath Diameter: Differences between Methods? A Pilot Study - Giger-Tobler, C.; Eisenack, J.; Holzmann, D.; Pangalu, A.; Sturm, V.; Killer, H. E.; Landau, K.; Jaggi, G. P. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: Quantification of the optic nerve sheath diameter is a promising approach for the detection of elevated intracranial pressure. The comparability of current methods is unclear. The objective of this study was to assess the relationship between optic nerve sheath diameter as measured with computed tomography, magnetic resonance tomography and ultrasound in patients without known optic nerve disease or increased intracranial pressure.Patients and Methods: 15 patients (60.8 [years] ± 16.73 SD; 7 female) with paranasal sinus pathology in whom computed tomography and magnetic resonance imaging were performed underwent optic nerve sheath diameter measurements by ultrasound, as well as an ophthalmological examination. Ultrasound-, computed tomography- and magnetic resonance imaging-derived maximal optic nerve sheath diameter values 3 mm behind the globe were compared.Results: Optic nerve sheath diameter measured (n = 30) by ultrasound (mean 6.2 [mm] ± 0.84 SD) was significantly (p < 0.01) higher than optic nerve sheath diameter in computed tomography (5.2 ± 1.11) or magnetic resonance imaging (5.3 ± 1.14). There was no significant (p = 0.24) difference between optic nerve sheath diameter measured in computed tomography and magnetic resonance tomography.Conclusions: The comparability of optic nerve sheath diameter measurements in patients without known optic nerve disease and assumed normal intracranial pressure appears to be given between computed tomography and magnetic resonance tomography, while comparability between ultrasound and computed tomography or magnetic resonance tomography seems to be less reliable.
Keywords: Optikusscheidendurchmesser; Computertomografie; Magnetresonanztomografie; Ultraschall